Rethinking Voter Coercion: The Realities Imposed by Technology - Benaloh, Josh (USENIX Journal of Election Technology and Systems (JETS), 2013)
When the Australian secret ballot was introduced in the 1850s, it not only provided privacy for those voters who wanted it, but it also effectively eliminated coercion by allowing no viable means for voters to prove their votes to third parties. In an environment where the privacy of voters is enforced by independent observers, coerced voters could freely express their true preferences while making their selections. In contrast, modern technologies render the traditional poll-site protections largely ineffective, and the limited remaining options for preserving these protections will almost certainly disappear in the not-too-distant future. Today, in-person voters routinely carry video recording equipment and other technologies that facilitate coercion into polls, and although not yet ubiquitous, inexpensive and unobtrusive wearable video recording devices are readily available. In view of these realities, it is appropriate to re-examine the efforts and countermeasures currently employed and explore what defenses are possible and reasonable against various forms of voter coercion